Radiation-Induced Meningioma Following Radiotherapy for Pituitary Adenonoma: A Case Report - Muhammed Nordin, Dr Ellyda (IIUM Medical Journal Malaysia, 2013)
It is well known that ionizing radiation has an onco-genetic activity and has been implicated in the causation of brain tumors. However, when a new growth appears adjacent to the site of previous tumor, the diagnosis is more toward recurrence. In addition to that, the possible cause might be overlooked, when it occurs many years after radiation treatment. We report a case of radiation-induced meningioma developed 20 years after the patient received radiotherapy for pituitary adenoma.